2012
DOI: 10.1007/s00192-012-1923-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injuries in vaginal delivery of twins: associated risk factors and comparison with singletons

Abstract: Risk factors of nulliparity, OP position, large fetal size, and instrumental delivery were shared by both twin and singleton deliveries. These data will be useful in counselling women carrying twins who intend to deliver vaginally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Another Canadian report 14 found the rate of OASI to be 2.8% in twin deliveries versus 4.4% in singletons, which is higher than our figures. They identified instrumental delivery as a risk factor for OASI 13,14 comparable to our own findings. Both studies are retrospective reports, one from a large maternity unit 13 and the second from a birth population database.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another Canadian report 14 found the rate of OASI to be 2.8% in twin deliveries versus 4.4% in singletons, which is higher than our figures. They identified instrumental delivery as a risk factor for OASI 13,14 comparable to our own findings. Both studies are retrospective reports, one from a large maternity unit 13 and the second from a birth population database.…”
Section: Discussionsupporting
confidence: 89%
“…It is noteworthy that 50% of sphincter injuries in our study included damage to the rectal mucosa (fourthdegree tears), considerably higher than the 90%:10% ratio reported in the literature. 13 Similarly, our institutional rates of third-and fourth-degree tears over the study period are 95.7 and 4.3%, respectively. While our analysis is limited by our smaller sample size, it does raise the possibility that while OASI is rarer in twin deliveries, the severity of these injuries may be worse.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…No data are available in the literature to compare such results, because twin or higher multiple pregnancies are often excluded from OASIS risk‐factor analysis. Two studies that investigated twin versus singleton births only found that risk factors were the same across both kinds of deliveries 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…There is limited research to date comparing women delivering twins with those delivering singletons in the risk of OASIS, mainly due to delivery at earlier gestations. Common risk factors in the two groups include nulliparity, fetal position, size, and instrumental delivery . However, it is still not clear whether twin deliveries, which are known to have longer second stage of labor and higher rates of obstetric interventions, expose women to higher risk of OASIS in comparison with singleton pregnancies provided the gestation age is similar.…”
Section: Introductionmentioning
confidence: 99%